Interleukin-17 in Behçet′s disease: relation with clinical picture and disease activity - Dina S Al-Zifzaf; Abir N Mokbel; Doaa M Abdelaziz (Egyptian Rheumatology and Rehabilitation, 2015)
Aim The aim of this study was to assess serum levels of interleukin-17 (IL-17) in patients with Behçet′s disease (BD) and to evaluate its relation to the clinical picture and disease activity. Patients and methods This case-control study was carried out on 38 patients with BD. A total of 20 age-matched and sex-matched healthy volunteers serving as the control group were also enrolled in this study. All patients were subjected to full history taking, thorough clinical examination, and clinical activity assessment using Behçet′s Disease Current Activity Form. Serum IL-17 levels were measured with enzyme-linked immunosorbent assay. Results Serum IL-17 levels were significantly elevated among BD patients. Patients with ocular involvement had higher IL-17 levels compared with those without; however, the difference did not reach statistical significance. Patients with neurological involvement had significantly higher IL-17 levels in their serum compared with those without neurological involvement and controls. Twenty-seven patients had active disease, whereas 11 patients had inactive disease. Serum IL-17 levels were significantly elevated in active BD patients. Patients with and without activity showed highly significant rise in IL-17 levels compared with healthy controls. There was no significant correlation between the amount of corticosteroids or colchicine being used and serum IL-17 levels. Conclusion IL-17 is elevated among BD patients and further increased with activity, ocular affection, and neuroinvolvement. Our findings suggest that IL-17 exerts an important role in the pathogenesis of BD, thus providing a promising target for novel therapy.